reflection of [tex]f(x)=\sqrt{x}[/tex] over the y axis we get [tex]g(x)=\sqrt{-x}[/tex]
Step-by-step explanation:
We need to find the reflection of f(x)=sqrt x over the y axis
So, reflection over y- axis
If the function f(x) is transformed over y-axis then the new function g(x) will be [tex]g(x)= f(-x)[/tex]
So, finding reflection of [tex]f(x)=\sqrt{x}[/tex] over the y axis we get:
[tex]g(x)=\sqrt{-x}[/tex]
So, reflection of [tex]f(x)=\sqrt{x}[/tex] over the y axis we get [tex]g(x)=\sqrt{-x}[/tex]
Keywords: Transformations
Learn more about Transformations at:
#learnwithBrainly